Enhancing the Effectiveness of Foreign Language Teaching through Innovative Methods and Digital Technologies (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The study aims to explore how innovative teaching methods and digital technologies contribute to improving the effectiveness of foreign language instruction. It focuses on identifying strategies that enhance learners’ motivation, engagement, and communicative competence.A mixed-method approach was adopted, combining quantitative surveys from 80 foreign language teachers with qualitative interviews from 20 instructors. Data were analyzed using descriptive statistics and thematic analysis to evaluate the effectiveness of different technological tools and interactive techniques.Results indicate that the integration of digital platforms such as Duolingo, Kahoot, and Google Classroom significantly increases students’ participation and retention. Moreover, the use of innovative methods like task-based learning, role-play, and project-based activities improves both linguistic competence and intercultural awareness. This study provides a novel framework that links pedagogical innovation with digital integration, offering a comprehensive model for 21st-century language education.The findings highlight the need for teacher training programs that incorporate technology-based pedagogies and emphasize communicative skills. Educational policymakers are encouraged to invest in digital infrastructure to enhance foreign language education quality. The study was limited to a small sample of instructors and learners; future research should examine larger, cross-cultural populations to validate the proposed framework.